Competition between Spin Excitation and Kondo Correlation in Magnetic Molecular Junctions: Theoretical Insight from First-principles-based Simulations - Zhuang, Qingfeng; Ye, Lyuzhou; Zheng, Xiao (Current Chinese Science, 2022)
In magnetic molecular junctions, the interactions between the local spin state at the transition- metal center and the conduction electrons from the electrodes or substrates can bring about many interesting strong correlation effects. Spin excitation and the Kondo effect are two representative phenomena, where the spin-unpaired d or f electrons plays the key role in forming these manybody states. This paper reviews the recent developments and applications of several first-principles methods in conjunction with the hierarchical equations of motion (HEOM) approach for the accurate simulation of magnetic molecular systems. The large-scale electrodes and substrates are treated by the density functional theory (DFT), while the properties of the magnetic center are studied by using the high-level complete active space self-consistent field method. The competition between the spin excitation and the Kondo effect are scrutinized by the HEOM approach. This combined DFT+HEOM method has proven to be useful for the accurate characterization of strongly-correlated magnetic molecular systems.
Keywords: kondo effect